Implementasi Kebijakan Alokasi Dana Desa di Desa Margasari Kecamatan Margasari Kabupaten Tegal - Kurniasih, Yuni; Warsono, Hardi; Priyadi, Budi Puspo (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2018)
Village Allocation Fund is a fund allocated by the Government for village in Tegal regency, which rises from the central and balance financial of fund received by district area. The Village Fund Allocation as one of village income source is expected to finance various development programme in the village so that it can improve the prosperity of the local community. Funds from districts are provided directly to villages to be managed by the Village Government. This research was meant to find out how the implementation of village allocation fund policy in Margasari village and knowing the influence factors of this implementation. This research using qualitative research methods. The results showed that the implementation of village allocation fund policy are still less effective that is seen from the precision implementation aspects such as society participation in planning process, performance of implementers, compatibility allocation with regulation, accountability of Village Allocation Fund, and benefit of Village Allocation Fund for village autonomy. The factors that influence the implementation such as communication, resource policy, disposition of the implementor and bureaucratic structure are still less optimal too. Based on these conclusions, the researcher recommend to the implementation agency should have high commitment and take maximal advantages of financial sources in order to achieve the purpose of this policy.